SELECTION OF APPROPRIATE GEODETIC EQUIPMENT FOR RECEPTION OF GNSS SIGNALS WHEN CONDUCTING HIGH-PRECISION MEASUREMENTS : SELECTION OF APPROPRIATE GEODETIC EQUIPMENT FOR RECEPTION OF GNSS SIGNALS WHEN CONDUCTING HIGH-PRECISION MEASUREMENTS - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is to make the right choice of GNSS receiver and related equipment, which will allow to achieve the required accuracy and high productivity with minimal material costs when conducting high-precision geodetic measurements.